A Butlerian Hauntology - Syed Mustafa Ali (ReOrient)
In this article, I engage with the backstory to Frank Herbert’s Dune saga, viz. The Butlerian Jihad, tracing its genealogy, and considering its possible relevance for thinking about and motivating an Islamicate response to artificial intelligence (AI) and cognate technologies. I argue the latter is a colonising phenomenon deployed along necropolitical lines against “the wretched of the earth”. My argument unfolds in a “nested structure”, beginning with an overview of The Butlerian Jihad and how it features in the Dune universe. I particularly examine how Herbert uses the term jihad and conflates it with crusade and explore a possible genealogy of The Butlerian Jihad , tracing its inspiration to “The Book of The Machines” in Samuel Butler’s novel Erewhon (1932 [1872]). Engaging with scholarly commentary on Butler’s work, I address implicit conceptions of class and race, particularly through the lenses of colonialism and the phenomenon of Other -ing. Considering Butler’s motivations for writing the novel, I explore how examining hauntology provides a pathway into a discussion of the potentialities of Luddism as a political project. Reframing Luddism along fugitive and decolonial lines, I conclude by exploring what it might mean to call for and enact a Butlerian Jihad today.